Sosialisasi Legalitas, Perizinan, Sertifikasi Halal, dan Standarisasi Produk UMKM - Arini, Arini; Mustika, Dama; Putri, Aprilia Milanda; Siagian, Elizabeth; Situmorang, Oktavyandi; Budiman, Andi Zahran; Lina, Nike; Br. Simamora, Feronika; Sinaga, Triani Angelika (Lembaga penelitian dan pengabdian kepada masyrakat, 2025)
This community service program aims to provide socialization about the legality, licensing, certification, and standardization of MSME products in Sialang Munggu Village. This activity is important to increase understanding and help manage legal aspects for SMEs. Legality is a crucial factor for public recognition, while licensing and certification increase consumer confidence. The method used is a direct lecture by Mr. Eka Saputra, SE from the Pekanbaru Industrial Service Standardization and Service Center. The results show that the participants' understanding is still low, but there is high enthusiasm for participating in the training. Capacity building is expected to encourage local economic growth and make SMEs the economy's driving force. In addition, this program also identifies obstacles faced by SMEs and proposes solutions to overcome these problems.